Aerosol indirect effects on glaciated clouds. Part 2: Sensitivity tests using solute aerosols. (23rd May 2016) - Kudzotsa, Innocent; Phillips, Vaughan T. J.; Dobbie, Steven
Abstract : Sensitivity tests were performed on a midlatitude continental case using a state‐of‐the‐art aerosol–cloud model to determine the salient mechanisms of aerosol indirect effects (AIE) from solute aerosols. The simulations showed that increased solute aerosols doubled cloud‐droplet number concentrations and hence reduced cloud particle sizes by about 20% and consequently inhibited warm rain processes, thus enhancing the chances of homogeneous freezing of cloud droplets and aerosols. Cloud fractions and their optical thicknesses increased quite substantially with increasing solute aerosols. Although liquid mixing ratios were boosted, there was, however, a substantial reduction of ice mixing ratios in the upper troposphere, owing to the increase in snow production aloft. The predicted total aerosol indirect effect was equal to −9.46 ± 1.4 W m −2 . The AIEs of glaciated clouds (−6.33 ± 0.95 W m −2 ) were greater than those of water‐only clouds (−3.13 ± 0.47 W m −2 ) by a factor of two in this continental case. The higher radiative importance of glaciated clouds compared with water‐only clouds emerged from their larger collective spatial extent and their existence above water‐only clouds. In addition to the traditional AIEs (glaciation, riming and thermodynamic), the new AIEs sedimentation, aggregation and coalescence were identified.